The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1101/gr.8.8.834
|View full text |Cite
|
Sign up to set email alerts
|

Direct Selection of Conserved cDNAs from the DiGeorge Critical Region: Isolation of a Novel CDC45-Like Gene

Abstract: We have used a modified direct selection technique to detect transcripts that are both evolutionary conserved and developmentally expressed. The enrichment for homologous mouse cDNAs by use of human genomic DNA as template is shown to be an efficient and rapid approach for generating transcript maps. Deletions of human 22q11 are associated with several clinical syndromes, with overlapping phenotypes, for example, velocardiofacial syndrome (VCFS) and DiGeorge syndrome (DGS). A large number of transcriptional un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Because of its involvement in VCFS, the deleted region on HSA 22q11.2 has been searched intensively for genes using a range of experimental approaches including exon trapping, cDNA selection, and gene prediction in silico based on human sequence comparison with EST databases (Gong et al, 1996;Lindsay et al, 196;Galili et al, 1997;McKie et al, 1998). It appears that most of the genes in the region have been discovered, providing a useful test set for comparison of sequence-based gene finding methodologies.…”
Section: Comparison Of Exon Prediction Approachesmentioning
confidence: 99%
“…Because of its involvement in VCFS, the deleted region on HSA 22q11.2 has been searched intensively for genes using a range of experimental approaches including exon trapping, cDNA selection, and gene prediction in silico based on human sequence comparison with EST databases (Gong et al, 1996;Lindsay et al, 196;Galili et al, 1997;McKie et al, 1998). It appears that most of the genes in the region have been discovered, providing a useful test set for comparison of sequence-based gene finding methodologies.…”
Section: Comparison Of Exon Prediction Approachesmentioning
confidence: 99%
“…As for a role in cognition, only one study reported that rs5992403 AA genotype carriers had higher preservation error scores in the Wisconsin Card Sorting test (Ota et al, 2013). CDC45 , the human homolog of a yeast cell cycle protein, is located in a genomic region telomeric and adjacent to UFD1L (McKie et al, 1998). Although the functional roles of the haplotypes of UFD1L and CDD45 that were significantly associated with cognitive impairment in schizophrenia remain unknown, further studies on the potential contribution of these genes to compromised neural networks in schizophrenia are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Murine cDNAs for the Idd (Taylor et al, 1997), Es2 (Rizzu et al, 1996), T10 (Halford et al, 1993), Hira (Mattei et al, 1994), and Cdcrel1 (Pnutl1) loci have been reported previously. Ctp, Tsk, Ufd1l, and Cdc4512 were obtained during cDNA selection (J. M. McKie et al, 1998). TBX1 (Trofatter et al, 1995;Chieffo et al, 1997), DGCR6 (Demczuk et al, 1996), COMT (Winquist et al, 1992), ZNF74 (Aubry et al, 1993), and CLTD (Sirotkin et al, 1996) probes were kind gifts from Dr. A. Buckler, Dr. S.…”
Section: Methodsmentioning
confidence: 99%
“…Hybridization analysis also allowed us to position the homologues of the genes for ARVCF (Sirotkin et al, 1997b), COMT (Heisterkamp et al, 1995), TMVCF (Sirotkin et al, 1997a), UFD1L (Pizzuti et al, 1997), and CDC45L2 (McKie et al, 1998). One gene, encoding a clathrin heavy chain-like protein (Sirotkin et al, 1996), was not mapped to this region of the murine genome.…”
Section: Comparative Mapping Of Human and Murine Genesmentioning
confidence: 99%